Analisis Pengawasan Pemungutan Pajak Air Tanah Dalam Meningkatkan Penerimaan Pajak di Inspektorat Jakarta Tahun Anggaran 2022 - Yuliana, Yuliana; Zahran, Wahidin Septa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Groundwater Tax with DKI Jakarta Provincial Regulation No. 17 of 2010 Article 1 paragraph 9 explains that groundwater tax is a tax on the collection and or utilization of groundwater. Based on observations and interviews, several problems were identified, namely that there are still many groundwater taxpayers who are not aware of their tax rights and obligations, less than optimal supervision from the government, especially the Inspectorate to groundwater taxpayers, lack of education or socialization to taxpayers, and lack of communication between the government and taxpayers. The research method used is qualitative with a descriptive analysis approach. In this study the authors used a qualitative approach because the problems raised were directly related to humans fundamentally which depended on research and observation. The results of the research that the author conducted then the author interpreted the answers given by the informants, either through interviews, or observing data or written documents related to the Analysis of Groundwater Tax Collection Supervision in Increasing Groundwater Tax Revenue by the Jakarta Inspectorate. The author uses Quible's theory in Khaerul Umam (2014) which consists of 4 indicators, namely supervised factors, where before supervision is carried out, officers who will carry out supervision should be given an understanding of what factors will be supervised, identification of expected results. Unclear identification of parameters regarding the desired results of the work activities carried out makes supervision will not run effectively, Performance measurement. Before actual results and desired results are compared, actual results must be measured. In some cases, this measurement also explains the quantity output, and Corrective action applications, where corrective action or evaluation needs to be taken to minimize the potential that occurs by implementing what is deemed necessary